Diagnostic accuracy of lung ultrasound score for bronchopulmonary dysplasia in preterm neonates: a systematic review and meta-analysis - Han, Chundi; Wang, Xiaohua; Pan, Minli; Huang, Xueyin (Frontiers in Pediatrics, 2025)
BackgroundBronchopulmonary dysplasia (BPD) remains common among preterm infants, yet diagnostic criteria rely on post-hoc oxygen requirements and radiography. Semiquantitative lung ultrasound (LUS) scoring offers a radiation-free, bedside alternative. We sought to determine the time-dependent diagnostic accuracy of LUS scores for BPD in preterm neonates.MethodsWe performed a systematic review and meta-analysis of studies reporting LUS scores in preterm neonates (born at <37 gestational weeks) with BPD. We searched five databases through June 2025. We stratified data into four postnatal age timepoints (days 1–3, 7, 14, and 21) and pooled them using bivariate random-effects models to estimate sensitivity, specificity, likelihood ratios, diagnostic odds ratios, and area under the hierarchical summary receiver-operating characteristic (HSROC) curve.ResultsWe included data from 22 studies (n = 2,038 infants) in our analyses. Within days 1–3 (10 studies; n = 1,326), LUS scores yielded sensitivity of 0.75 (95% CI, 0.62–0.85), specificity of 0.74 (0.63–0.82), and AUROC of 0.81. At day 7 (15 studies; n = 1,790), sensitivity and specificity results improved to 0.78 (0.71–0.84) and 0.83 (0.78–0.87), respectively; and AUROC to 0.88. Day 14 performance was similar to that at day 7 (sensibility, 0.78; specificity, 0.84; AUROC, 0.87). By day 21 (4 studies; n = 619), the performance accuracy peaked [sensibility, 0.85 [0.73–0.92]; specificity, 0.86 [0.71–0.94]; and AUROC, 0.92]. Overall, positive likelihood ratios rose from 2.8 to 6.3 and negative ratios fell from 0.33 to 0.18. The heterogeneity decreased at the later intervals.ConclusionThe diagnostic accuracy of LUS scoring for BPD improved from the first through the third weeks of life, approaching optimal levels by day 21. These findings support the integration of serial LUS assessments into neonatal care plans to enable earlier, non-invasive BPD diagnosis.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251085780, PROSPERO CRD420251085780.